Hyperpigmentation and thickening of skin with callosity formation over dorsum of both feet and healed ulceration over left lateral malleolus in a patient with type 2 diabetes performing prolonged prayers. Issue 3 (May 2020) - Gupta, Anchal; Ghosh, Amerta
Abstract: Many types of skin lesions have been described in patients with diabetes, but prolonged prayer-induced hyperkeratosis and callous formation are rare. We describe such lesions in a 62-year-old Muslim patient with uncontrolled glycemia who practiced prolonged, repeated religious prayers in sitting position causing significant pressure over dorsum of both ankles. He developed prayer-induced callous formation on dorsum of both ankles, with more thickening and a healed ulcer on left. Prayer-induced skin lesions should be carefully managed in patients with diabetes, who are more vulnerable for infections and gangrene due to as venous/arterial insufficiency and peripheral neuropathy. Highlights: We describe prayer-induced skin lesions in a 62 -year -old Muslim man who practiced prolonged and repeated prayers. The lesions were in the form of thickening of skin, hyperpigmentation, callous formation on dorsum of both feet and healed ulcer over callous left foot. These lesions should be carefully identified and managed in patient with diabetes who are already vulnerable to develop foot-related complications.